(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The erudite software mechanism of content-based image representation and retrieval is crystal clear that it is perception-based approach. Here it main pragmatic concept is texture images and propose to model their textural concept. The main dexterous melted to estimate textural feature an namely Complexity, texture strength, coarseness, directionality, contrast, busyness and Textron. The ineffable computational measures are based on autocorrelation function (Associated with original image) An anchored comparison is taken among it statistical and structural methods of texture representation. It elicits which features given vivid performance.